Asymmetric synthesis of γ-chloro-α,β-diamino- and β,γ-aziridino-α-aminoacylpyrrolidines and -piperidines via stereoselective Mannich-type additions of N-(diphenylmethylene)glycinamides across α-chloro-N-sulfinylimines - Callebaut, Gert; Mangelinckx, Sven; Van der Veken, Pieter; Törnroos, Karl W.; Augustyns, Koen; De Kimpe, Norbert (Beilstein Journal of Organic Chemistry, 2012)
The asymmetric synthesis of new chiral γ-chloro-α,β-diaminocarboxylamide derivatives by highly diastereoselective Mannich-type reactions of N-(diphenylmethylene)glycinamides across chiral α-chloro-N-p-toluenesulfinylaldimines was developed. The resulting (SS,2S,3S)-γ-chloro-α,β-diaminocarboxylamides were formed with the opposite enantiotopic face selectivity as compared to the (SS,2R,3R)-γ-chloro-α,β-diaminocarboxyl esters obtained via Mannich-type addition of analogous N-(diphenylmethylene)glycine esters across a chiral α-chloro-N-p-toluenesulfinylaldimine. Selective deprotection under different acidic reaction conditions and ring closure of the γ-chloro-α,β-diaminocarboxylamides was optimized, which resulted in Nα-deprotected syn-γ-chloro-α,β-diaminocarboxylamides, N-sulfinyl-β,γ-aziridino-α-aminocarboxylamide derivatives, a trans-imidazolidine, and an Nα,Nβ-deprotected syn-γ-chloro-α,β-diaminocarboxylamide.
Keywords: asymmetric synthesis; diaminoacid derivatives; Mannich-type addition; N-sulfinylimines; stereoselectivity